Korczak’s postulate and justification for the child’s right to respect. Resume on pedagogical deontology and pedagogy of asylum - Włodarczyk, Rafał (Forum Pedagogiczne, 2020)
Theaim of this paper is to analyze the ethical justification of the norm of respect owed to children because of their particular social situation proposed by Janusz Korczak in his famous essay The Child’s Right to Respect. Recognition and proper application of this norm requires reviewing and understanding of its basics.